Enhanced Red Upconversion Emission, Magnetoluminescent Behavior, and Bioimaging Application of NaSc0.75Er0.02Yb0.18Gd0.05F4@AuNPs Nanoparticles - Rai M.; Singh S.K.; Singh A.K.; Prasad R.; Koch B.; Mishra K.; Rai S.B. (My University, 2025)
The present study reports significant enhancement in the red upconversion emission of Er3+ in NaSc0.8Er0.02Yb0.18F4 upconversion nanoparticles (UCNPs), via a two step process, (i) codoping of Gd3+ ion at Sc3+ site and (ii) attaching gold nanoparticles (AuNPs) at the surface of these codoped nanostructures, and further probes the use of these Gd:UCNPs@AuNPs for bioimaging application. The Gd3+ codoping tailors the particle size (reduces) of UCNPs and bring out Er3+-Yb3+ ion pair in close proximity, which promotes the cross relaxation mechanism and boosts the population in red emitting level 4F9/2. Further, attachment of AuNPs on the surface of UCNPs gives 2-fold advantages, that is, reduction in green band (through resonance energy transfer with efficiency 31.54%) and enhancement in red band (through plasmonic effect). It gives red to green (R/G) ratio nearly 20:1 (almost single band red UC), which is quite promising for imaging application. In addition to this, codoping of Gd3+ enhances the magnetic moment appreciably and the obtained magnetic moment for NaSc0.75Er0.02Yb0.18Gd0.05F4 UCNPs (∼1.7 emu/g) is close to the reported values for bioseparation in case of NPs. This shows the potential of the material for multimodal (optical and magnetic both) imaging application. These magnetoluminescence particles were found safe up to 1 mg/mL dose as assessed by cytotoxicity measurement in human cervical cancer (HeLa) and lung cancer (A549) cells. Ultrafine nanoparticles, transparent, and stable colloidal solution and the unique red UC emission endow these NPs as optical probe for imaging applications. © 2015 American Chemical Society.